Structural changes and organisations in the print media markets of post-communist East Central Europe - Gulyas, Agnes (Javnost (Ljubljana), 1999)
The transformation of the media in East Central Europe during the post-communist period is featured by different economic, social, political and cultural changes. This article looks at two specific issues: structural and ownership changes in the print media markets of the Czech Republic, Hungary and Poland since 1989. Using analytical tools of media economics research characteristics of market structures, such as development of supply and demand, concentration, barriers to market entry, vertical integration, are analysed. It is argued that post-communist print media markets became less concentrated compared to the communist era, and due to frequent ownership changes market concentration levels fluctuated but not increased substantially during the 1990s. The article also gives an overview of the main characteristics of local and foreign-owned media companies. The development and reasons behind foreign investments are examined, as foreign ownership played a significant role in the print media sectors of the three countries during the post-communist era. It is argued that foreign media ownership is part of the general internationalisation of post-communist media in East Central Europe, which process has both negative and positive effects.
Keywords: Eastern Europe; Vzhodna Evropa; Central Europe; Srednja Evropa; mass media; množični mediji; časopisi; tranzicija; privatizacija